PELAKSANAAN PENEGAKAN HUKUM TERHADAP DELINKUEN ANAK DALAM PERKARA ANAK NAKAL BERDASARKAN UNDANG-UNDANG NOMOR : 3 TAHUN 1997 TENTANG PENGADILAN ANAK DI KOTA YOGYAKARTA DAN PENGEMBANGAN KONSEP KEADILAN RESTORATIF DENGAN CARA DIVERSI DALAM RANCANGAN UNDANG-UNDANG PENGADILAN PIDANA ANAK DI INDONESIA - , ZAHRU ARQOM, Sigid Riyanto, S.H., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Act No. 3/1997 known as The Juvenile Court, had a retributive justice model approach which is not guarantee in protection and rehabilitation for the juvenile delinquency. Giving an imprisonment punishment (penal system) became a dominant colour in this model. In contrary, law concept has other approach, known as Restorative Justice model. This alternative system is promoting an educative punishment rather than sending chidren to the jail. The main purposed is protecting the basic rights of children as juvenile delinquency. As a legal concept, Restorative Justice model is not literally and textually wrote in The Juvenile Court Law yet. Therefore, need to be observed, the influence and implementation of this concept in crime case, reflected or not reflected in the Court Decission for juvenile case under the Act No. 3/1997 and how to develope the restorative justice concept in Indonesia. The object of This research is the Special Judge for the juvenile deliquency and Nine Court decission of juvenile delinquency case at Yogyakarta District Court during 2010. The Methodology to use samples in this research is random sampling methode. This research also observe draft of The juvenile criminal court act as an amandement current law to revised Act No.3/1997. Based on data, the draft concept was adopted from the principles of The UN Declaration of the Childrens Rights Number : 1386 date 20th November 1959 and The UN Declaration of The Standard Minimum Rules for the Administration of Juvenile Justice Number : 40/33 date 20th November 1985, or as known as The Beijing Rules which is Indonesian Government had ratificated under The President Decission Number : 36/1990. This research revealed a surprising facts. Base on the main data, all of the suspicion in Juvinele deliquency case, had been sentenced for the imprison punishment and no one of them was sentence to rehabilitation punishment. It means that restorative justice is not reflected in the decission of juvenile delinquency case at Yogyakarta District Court during 2010. Meanwhile, The draft of amandement of the juvenile court law is containt of the rule of how to mainstraiming a protection and rehabilitation model. This draft also equiped with a diversion rule in every steps of process in criminal justice system. From investigation level by police investigator, then to prosecution level by public prosecutor, and finally in the level of court proceeding as the implementation of restorative justice.